Expression of three GnRH receptors in specific tissues in male and female sea lampreys Petromyzon marinus at three distinct life stages - Hall, Jeffrey A.; Decatur, Wayne A.; Daukss, Dana M.; Hayes, Mary K.; Marquis, Timothy J.; Morin, Scott J.; Kelleher, Thomas F.; Sower, Stacia A. (Frontiers in Neuroscience, 2013)
Two recently cloned gonadotropin-releasing hormone (GnRH) receptors (lamprey GnRH-R-2 and lamprey GnRH-R-3) along with lamprey (l) GnRH-R-1 were shown to share similar structural features and amino acid motifs common to other vertebrate receptors. Here we report on our findings of RNA expression of these three GnRH receptors in the three major life stages (larval, parasitic, and adult phases) of the sea lamprey, Petromyzon marinus, a basal vertebrate. For each stage, we examined the expression of messenger RNA encoding the receptors in the brain, pituitary, gonad, heart, muscle, liver, eye, intestine, kidney, skin, thyroid, gill, and endostyle by RT-PCR. In adult lampreys, the spatial expression of the three receptors in the brain and pituitary was investigated by in situ hybridization. In general, the receptors were more widely expressed in adult tissues as compared to parasitic-phase tissues and least widely expressed in the larval tissues. There were noted differences in male and female lampreys in the adult and parasitic phases for all three receptors. The data showed the presence of all three receptor transcripts in brain tissues for adult and parasitic phases and all three receptor transcripts were expressed in the adult pituitaries, but not in the parasitic pituitaries. However, in the larval phase, only lGnRH-R-1 was expressed in the larval brain and pituitary. In situ hybridization revealed that lGnRH-R-2 and -3 were expressed in the pineal tissue of adult female lampreys while lGnRH-R-1 was expressed in the pineal in adult male lampreys, all restricted to the pineal pellucida. In summary, these data provide an initial comparative analysis of expression of three lamprey GnRH receptors suggesting differential regulation within males and females at three different life/reproductive stages.